Continuity of the solutions of one-dimensional boundary-value problems in Hölder spaces with respect to the parameter - Maslyuk, H. O. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We introduce the most general class of linear boundary-value problems for systems of ordinary differential equations of order r ≥ 2 whose solutions belong to the complex Hölder space C^n+r,α ([a, b]), where n Z_+, 0 < α ≤ 1 и [a, b] R, and [a, b] R. We establish sufficient conditions under which the solutions of these problems continuously depend on the parameter in the H¨older space C^n+r,α ([a, b]).